2010
DOI: 10.1128/iai.00699-10
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica Infection and Secreted Proteins Proteolytically Damage Enteric Neurons

Abstract: The enteric protozoan parasite Entamoeba histolytica causes amebic colitis through disruption of the mucus layer, followed by binding to and destruction of epithelial cells. However, it is not known whether ameba infections or ameba components can directly affect the enteric nervous system. Analysis of mucosal innervations in the mouse model of cecal amebiasis showed that axon density was diminished to less than 25% of control. To determine whether amebas directly contributed to axon loss, we tested the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Conversely, other pathogens (eg, Entamoeba histolytica) can elicit neurodegeneration without altering EGCs. 60 Concerning functional bowel disorders, EGC abnormalities have been detailed in 2 severe gut dysmotility disorders: slow transit constipation (STC)/colonic inertia and megacolon. STC refers to a subset of patients characterized by a marked delay of gut transit that usually does not or responds poorly to medical treatment.…”
Section: Changes In Egcs In Gastrointestinal Diseasesmentioning
confidence: 99%
“…Conversely, other pathogens (eg, Entamoeba histolytica) can elicit neurodegeneration without altering EGCs. 60 Concerning functional bowel disorders, EGC abnormalities have been detailed in 2 severe gut dysmotility disorders: slow transit constipation (STC)/colonic inertia and megacolon. STC refers to a subset of patients characterized by a marked delay of gut transit that usually does not or responds poorly to medical treatment.…”
Section: Changes In Egcs In Gastrointestinal Diseasesmentioning
confidence: 99%
“…The cause of this phenomenon is likely complex and multifactorial; however, it is possible that the differences in regulation over time are due to the kinetics of E. histolytica infection. It has been previously suggested that E. histolytica establishes infection sequentially, beginning with attachment to and degradation of the mucus layer, followed by invasion and destruction of the epithelial layer, and finally invasion into the lamina propria and damage of the enteric nervous system (67)(68)(69). Thus, it is likely that at early time points during infection (i.e., at 12 h) transcriptional changes are due to superficial invasion of the mucosa, while later responses represent deeper invasion and more tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of SNAP-25 in the CNS has been extensively studied, little data are available concerning SNAP-25 expression and localization in the human and rat ENS. Previous studies have used SNAP-25 as pan-axonal marker of the ENS in murine cecum and colon (Lourenssen et al 2010;Poli et al 2001) or to characterize membrane specialization between nerve terminals and intestinal cells of Cajal in the murine stomach (Beckett et al 2005). However, a systematic investigation of SNAP-25 in the adult ENS is still missing.…”
Section: Introductionmentioning
confidence: 96%